Atlas of Postsurgical Neuroradiology Imaging of the Brain, Spine, Head, and Neck - Ginat, Daniel Thomas; Westesson, Per-Lennart A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The number of surgical procedures performed on the brain, head, neck, and spine has increased markedly in recent decades. As a result, postoperative changes are being encountered more frequently on neuroradiological examinations and constitute an important part of the workflow. However, the imaging correlates of postsurgical changes can be unfamiliar to neuroradiologists and neurosurgeons and are sometimes difficult to interpret. This book is written by experts in the field and contains an abundance of high-quality images and concise descriptions, which should serve as a useful guide to postsurgical neuroradiology. It will familiarize the reader with the various types of surgical procedure, implanted hardware, and complications. Indeed, this work represents the first text dedicated to the realm of postoperative neuroimaging. Topics reviewed include imaging after facial cosmetic surgery; orbital and oculoplastic surgery; sinus surgery; scalp and cranial surgery; brain tumor treatment; psychosurgery, neurodegenerative surgery, and epilepsy surgery; skull base surgery including transsphenoidal pituitary resection; temporal bone surgery including various ossicular prostheses; orthognathic surgery; surgery of the neck including the types of dissection and flap reconstruction; CSF diversion procedures and devices; spine surgery; and vascular and endovascular neurosurgery.
Introduction -- Brain: Burr holes/craniotomy/craniectomy/tumor resection. Devices -- Skull base: Anterior craniofacial resection. Pituitary tumor resection. Craniopharyngioma resection. Suprasellar cyst fenestration. Encephalocele repair. Temporal bone. Complications -- Craniofacial: Craniosynostosis repair. LeFort osteotomy. Sagittal split. Fracture repair. Septoplasty. Cosmesis. Complications -- Head and Neck: Neck. Mandible. Pharynx. Orbit. Flap reconstruction. Thyroidectomy. Parathyroidectomy. Paranasal sinuses. Devices -- Spine: Variety of procedures and hardware. Spine stimulation. Kyphoplasty/vertebroplasty/sacroplasty. Failed back surgery syndrome -- Vascular: Variety of clips, coils, stents. Aneurysm treatment. AVM/AVF/covernoma treatment. Embolectomy. Angioplasty. Synangiosis. Venous sinus skeletonization. CEA. Carotid-axillary bypass. Complications -- CSF shunts: Ventriculoperitoneal shunts. Lumboperitoneal shunts.
Keywords: Medicine; Radiology, Medical; Neurosurgery; Head -- Surgery; Medicine & Public Health; Neuroradiology; Neurosurgery; Head and Neck Surgery